Pertanggungjawaban Pidana atas Tindak Pidana Pelecehan Verbal melalui Media Sosial - Aena Linda Mustika; Setiyono Setiyono; Muhari Santoso; Nahdiya Sabrina (University of Merdeka Malang, 2021)
Sexual crimes are becoming more frequent nowadays, one form of which is sexual harassment through verbal means through social media. Sexual harassment through verbal means that occurs is usually carried out directly, such as whistling, shouting at someone, gestures that appear seductive, and others. As the technology of sexual harassment evolves in the form of writing / typing, seduction, flirting on social media (chat, direct message, and comments), this is of course still as disturbing as direct harassment. The act of verbal sexual harassment through social media is an act against the law that violates Article 27 paragraph (1) of the ITE Law which does not specifically regulate in detail the types of sexual harassment acts. Crimes against decency areregulated in the Criminal Code but not specifically because the Criminal Code does not mention the term sexual harassment. The bill on the elimination of sexual violence that contains sexual harassment has not yet been passed, while the law that was enacted to prevent acts of verbal sexual harassment through social media is still limited.